Influence of microphone housing on the directional response of piezoelectric MEMS microphones inspired by Ormia ochracea - Bauer, Ralf; Zhang, Yansheng; Jackson, Joseph C.; Whitmer, William M.; Brimijoin, W. Owen; Akeroyd, Michael A.; Uttamchandani, Deepak; Windmill, James F.C. (IEEE, 2017)
The influence of custom microphone housings on the acoustic directionality and frequency response of a multi-band bio-inspired MEMS microphone is presented. The 3.2mm by 1.7mm piezoelectric MEMS microphone, fabricated by a cost-effective multi-user process, has four frequency bands of operation below 10 kHz, with a desired first order directionality for all four bands. 7x7x2.5 mm3 3D-printed bespoke housings with varying acoustic access to the backside of the microphone membrane are investigated through simulation and experiment with respect to their influence on the directionality and frequency response to sound stimulus. Results show a clear link between directionality and acoustic access to the back cavity of the microphone. Further, there was a change in direction of the first order directionality with reduced height in this back cavity acoustic access. The required configuration for creating an identical directionality for all four frequency bands is investigated along with the influence of reducing the symmetry of the acoustic back cavity access. This work highlights the overall requirement of considering housing geometries and their influence on acoustic behavior for bio-inspired directional microphones.